Effects of the application of biodegradable coatings on post-harvest tomato conservation (Research, Society and Development, 2022)
Tomato (Solanum lycopersicum L.) culture has great economic and social importance for Brazil. However, tomato presents itself as a fruit of high perishability with short shelf life, which requires methods for its postharvest conservation, for example, the use of biodegradable coatings. Therefore, the objective of this work was to evaluate the effect of biodegradable coatings based on cassava starch and glycerol, on the postharvest quality of tomato variety Italian hybrid "TY" at room temperature. The experiment was conducted in the Laboratory of Storage of Agricultural Products (LAPA), Federal University of São Francisco Valley (UNIVASF). The tomatoes were selected, washed and coated with manioc starch and glycerol solutions at concentrations of 5% and 1% respectively, stored at room temperature for twelve days and evaluated every two days for loss of mass, fruit firmness, hydrogen potential, total soluble solids, total titratable acidity, ratio of soluble solids to total titratable acidity and peel color. The experimental design was entirely randomized in a 3 x 7 factorial scheme (coatings x storage time), with five repetitions per treatment. The results were submitted to variance analysis, regression analysis and the means were compared using Tukey's test at 5% probability. The concentrations used in the preparation of the coatings FEC 5% and FEC 5% + GLIC 1% stood out in the preservation of some quality attributes, such as loss of mass, firmness, acidity and color of the peel. The coatings used were characterized as possible alternatives to preserve the postharvest quality of tomatoes when kept at room temperature.